Personalized Medicine in the Field of Inflammatory Skin Disorders - Tampa, Mircea; Neagu, Monica; Caruntu, Constantin; Georgescu, Simona Roxana (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Skin inflammation is associated with a wide range of conditions which represent major health issues worldwide. Skin and mucosal surfaces represent the primary interface between the human body and the environment, susceptible to numerous factors whose action results in diseases produced by chemical substances, mechanical trauma, microbial agents, radiation, etc. Inflammation, a complex network of interactions between soluble molecules and cells, represents the main modality of the skin's response to injuries. Numerous studies have revealed close links between chronic inflammation, oxidative stress, and carcinogenesis. Chronic inflammation induces the activation of various cell types and an increase in the production of reactive oxygen species, promoting the initiation of a malignant process. Identifying specific biomarkers is essential for understanding molecular mechanisms and developing therapies appropriate to the patient's characteristics.Personalized medicine is an emerging field of medicine that has the potential to predict which therapy will be safe and efficacious for specific patients using an individual's genetic profile to guide decisions regarding the diagnosis, treatment, as well as prevention of disease. This book gathers articles that present recent advancements in research involving the mechanisms that underlie the development of inflammatory skin disorders, skin and mucosal inflammation in general.